Processed line aerogravity data over Ellsworth Land region (2001) - Jones, P.; Ferraccioli, Fausto; Smith, Andrew (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
During the 2001-02 field season a regional survey was flown on a 10 km line spacing grid over the drainage basin of the Rutford Ice stream (West Antarctica), as part of the TORUS (Targeting ice stream onset regions and under-ice systems) project. We present here the processed line aerogravity data collected using a LaCoste & Romberg air-sea gravity meter S83 mounted in the BAS aerogeophysically equipped Twin Otter aircraft. Data are provided as XYZ ASCII line data. : Aerogravity measurements were acquired with a modified LaCoste and Romberg air/sea gravimeter. The aircraft acceleration was calculated from dual frequency, carrier phase measurements using geodetic receivers. Free-air gravity anomalies were calculated, and a low-pass filter was applied to the data. Cross-over analysis indicates the free-anomaly field is accurate to 3.7 mGals for wavelengths greater than 9 km. Processing steps: 1/ Calculate observed gravity. True spring tension (ST_real) is calculated from the posted spring tension (ST) correcting for the fact that for this survey the true spring tension approaches the posted value at 38 mGal per second. Beam velocity (Beam_vel) is derived from raw beam position (RB) assuming a centred difference approximation. Relative gravity (rec_grav) = (Spr_tens_real+((beam_vel)*k_fac)+CC)*scale_value, k_fac=30, meter scale value =0.9966. Still readings (Still) are in mGal and were calculating assuming a 2nd order best fit to the approximately linear drift of the meter observed at the tie down points. Airborne absolute gravity values (Abs_grav) = Rec_grav- Still + Base 2/ Corrections to derive free air anomalies (disturbances). Vertical acceleration (VaccCor) is calculated as 2nd derivative of flight altitude (Height_WGS1984), with a 3 point mean filter applied after differencing to reduce short wavelength noise. Eotvos correction (EotvosCor) follows (Harlan, 1968). Latitude correction (LatCor) = 978.03185(1+0.005278895 sin2Lat- 0.000023462 sin4Lat) (IUGG 1967). Free air correction (FaCor) = 0.3086*Height_WGS1984. NOTE subsequent free air values are defined as gravity disturbances in geodesy, as they are referred to the ellipsoid (Hackney and Featherstone, 2003). Horizontal acceleration correction (HaccCor). For this survey the approximation of (Swain, 1996) was used, assuming a damping factor of 0.707, and a platform period of 4 minutes. 3/ Free air anomaly and filtering. Free air anomaly (Free_air) = Abs_grav-VaccCor+EotvosCor+FaCor-LatCor-(0.5*HaccCor) Filtered free air anomaly (FAA_filt) used 9 km 1/2 wavelength space domain kernel filter (Holt et al., 2006). Final free air data (FAA_clip) was produced by manually masking turns, start and end of lines, and other regions of noisy data. Levelling correction (level_cor) includes both statistical (line and tie) and microleveling (line only) of free air data. FAA_level includes data after levelling. Upward continued free air anomaly (FAA_1976m) was produced by upward continuing free air data from the collected flight altitude to 1976 m. Channel description: Basic Channels Date UTC date (YYYY/MM/DD) Time UTC time (HH:MM:SS.SS) FlightID Sequential flight number and survey ID e.g. W12 Line_name Line Number e.g. LW200.1:12 Lon Longitude WGS 1984 Lat Latitude WGS 1984 x x projected meters* y y projected meters* Height_WGS1984 Aircraft altitude (meters) in WGS 1984 Raw gravity Channels ST Spring Tension (meter units) CC Cross Coupling (meter units) RB Raw beam position (Mv) XACC Cross axis accelerometer (Mv) LACC Long axis accelerometer (Mv) Still Airborne meter still reading value (mGal) Base Absolute gravity reference, from land gravity (mGal) Calculation Channels St_real True Spring tension value (meter units) Beam_vel Gravity meter beam velocity (Mv/sec) Rec_grav Recalculated relative gravity (mGal) Abs_grav Calculated absolute gravity (mGal) VaccCor Vertical acceleration correction (mGal) EotvosCor Eotvos correction (mGal) LatCor Latitude correction (mGal) FaCor Free air correction (mGal) HaccCor Horizontal acceleration correction (mGal) Free air Channels FAA Un-filtered free air anomaly (mGal) FAA_up1976 Filtered free air anomaly upward continued to a height of 1976 m (mGal). *Projected coordinates (x and y) are in Lambert conic conformal with two standard parallels defined as follows: Latitude of natural origin: -71 Longitude of natural origin: 0 Scale factor at natural origin 0.994 False easting 0 False northing 2082760.109 : The following parameters have no values: St_Real, Abs_Grav, EotvosCor, LatCor, FaCor, HaccCor